Implementation Of The Indonesia-Korea Comprehensive Economic Partnership Agreement (IK-CEPA): An Analysis Of Strategic And Economic Impacts On Bilateral And Regional Relations - Syuryansyah Syuryansyah; Bagaskara Sagita Wijaya (SOSIO DIALEKTIKA, 2024)
The Indonesia-Korea Comprehensive Economic Partnership Agreement (IK-CEPA) represents a strategic move to enhance bilateral economic relations and maximize the potential of both countries. This study employs qualitative analysis and literature review methods to assess the strategic impacts of IK-CEPA, focusing on diplomatic, regional, and economic aspects. Diplomatically, IK-CEPA strengthens bilateral ties with South Korea, reflecting a positive shift in South Korea's view of Indonesia as a strategic partner. Regionally, the agreement contributes to strengthening economic cooperation and improving Indonesia's competitiveness in the global market. Economically, IK-CEPA has significant effects on bilateral trade and capital flows by reducing tariff barriers and creating new investment opportunities, particularly in sectors such as automotive and renewable energy. Major challenges include limited information and financial access for SMEs, while opportunities involve increased exports, digitization of SMEs, and utilization of advanced technology. The study concludes that IK-CEPA offers substantial benefits for Indonesia's economy by enhancing the country's position in the international market and driving domestic economic growth.